Total knee arthroplasty and physical therapy for arthropathy in alkaptonuria: A 4-year follow-up case report - Wu, Linfeng; Hu, Yu (Frontiers in Surgery, 2023)
Introduction: Alkaptonuria is a rare autosomal recessive metabolic disorder which leads to accumulation of homogentisic acid in the body Case Presentation: We report a rare case of an alkaptonuria-related knee arthritis who underwent left total knee arthroplasty and received postoperative systematic physical therapy in a 57-year-old male patient. The patient has suffered from bilateral knee pain for over 4 years. The patient developed melanin pigmentation on the skin of the whole body, especially on the face and auricle. He self-reported that fresh urine was normal color but after standing overnight, the color deepened to black or soy color. He underwent routine urine examination for many times, but no obvious abnormality was found. The patient has suffered from low back pain for more than 20 years. He had been considered for lumbar disc herniation and ankylosing spondylitis after many in-hospital visits. After symptomatic medication, there was no obvious relief. We followed the patient for 4 years after surgery. Result: The patient presented with pain relief and enhanced range of motion at the 4-year follow-up. The improvements of daily living and the pain relief suggest that the surgery is appropriate for this rare disease. Conclusion: It is rare that the knee pain is diagnosed as alkaptonuria. After total knee arthroplasty and physical therapy, the patient had a good outcome. This case provides experience for the diagnosis and treatment of alkaptonuria-related knee arthritis.